Changes in Metabolite and Protein Expression Profiles of Atypical Dark-cutting and Normal-pH Beef - Kiyimba, Frank (J Anim Sci, 2021)
The color of meat is an important deciding factor in consumers’ assessment of meat quality. To meat buyers, the bright cherry-red color of meat indicates freshness and wholesomeness. However, atypical dark-cutting beef represents dark-colored meat with a muscle pH between 5.6 and 5.8. Although previous studies have indicated that the ultimate pH of atypical dark-cutting beef is greater than normal, the mechanistic basis for the occurrence is not clear. Therefore, the objective of this study was to identify protein and metabolite profiles of normal and atypical dark-cutting beef. Longissimus thoracic (LT) muscles from 12 different animals (6 atypical dark-cutters and 6 normal-pH beef) were analyzed by comparing changes in metabolites and protein profiles using GC-MS non-targeted metabolomics and LC-MS/MS-based proteomics, respectively. Metabolomics analysis showed down-regulation of glycolytic metabolites such as glucose-6-phosphate, lactose, and glucose, indicating a reduced capacity to accumulate lactate postmortem in atypical dark-cutters compared with normal-pH beef. Mass spectrometry analysis identified 66 proteins with significant changes in protein expression profiles (P < 0.05) between atypical and normal-pH beef. Of these, 22 proteins were up-regulated while 14 were down-regulated in atypical dark-cutting beef. Functional annotation and protein-protein interaction network analyses revealed that up-regulated proteins such as NADH ubiquinone oxidoreductase subunit A7, ATPase Na+/K+ transporting subunit alpha 2, 3-oxoacid CoA-transferase 1, cytochrome b5 reductase 3, actinin alpha 4, tropomyosin 2, heat shock protein beta-7, and DnaJ heat shock protein family (Hsp40) member B4 are involved in energy synthesis, muscle contraction and stress responses. By contrast, down-regulated proteins, including phosphofructokinase, glycogen phosphorylase, amylo-alpha-1,6-glucosidase, phosphorylase kinase regulatory subunit alpha and gamma are involved in glycogen metabolism. In summary, lower glycolytic metabolites and glycogen degradation enzymes are associated with differences in muscle pH and color of atypical dark-cutting beef.